2022
DOI: 10.3390/nu14132752
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside and Dihydronicotinic Acid Riboside Synergistically Increase Intracellular NAD+ by Generating Dihydronicotinamide Riboside

Abstract: Through evolution, eukaryote organisms have developed the ability to use different molecules as independent precursors to generate nicotinamide adenine dinucleotide (NAD+), an essential molecule for life. However, whether these different precursors act in an additive or complementary manner is not truly well understood. Here, we have evaluated how combinations of different NAD+ precursors influence intracellular NAD+ levels. We identified dihydronicotinic acid riboside (NARH) as a new NAD+ precursor in hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…NQO2 differs from NQO1 in that it requires NRH as a coenzyme [10]. NRH is a precursor of NAD [37] and increases intracellular NAD levels [38,39]. Our experiments showed that an increase in NQO2 following HOXA11-AS knockdown resulted in a decrease in NAD concentration.…”
Section: Discussionmentioning
confidence: 63%
“…NQO2 differs from NQO1 in that it requires NRH as a coenzyme [10]. NRH is a precursor of NAD [37] and increases intracellular NAD levels [38,39]. Our experiments showed that an increase in NQO2 following HOXA11-AS knockdown resulted in a decrease in NAD concentration.…”
Section: Discussionmentioning
confidence: 63%
“…NAD + is present in the kidney at concentrations ranging from 0.3 to 1 mmol/kg of tissue, which is comparable to concentrations found in liver and muscle [22,26,27]. In this section, we detail the NAD + biosynthetic pathways from different precursors in PTECs, and describe its cellular roles in renal tissue, before explaining the alterations in NAD + homeostasis occurring during premature renal aging and CKD.…”
Section: Nad + Biology In the Kidneymentioning
confidence: 84%
“…NMNH has also been shown to increase NAD + levels after a dephosphorylation step to NRH prior to its incorporation into the intracellular space [54]. A final reduced precursor, dihydronicotinic acid riboside (NARH) can act synergistically with nicotinamide riboside (NR) to increase NAD + through their conversion to NRH [26]. The greater effectiveness of NRH compared to NR as an NAD + booster could be based on both the higher enzymatic phosphorylation rate of AK compared to NRK1, and the fact that NRH is not or less degraded to NAM in plasma, which is the case for NR [27].…”
Section: Amidated Salvage Pathwaysmentioning
confidence: 99%
“…NRH is a reduced form of NR, a new and very efficient fifth pathway for NAD + synthesis. Unlike NR, which is phosphorylated to NMN by Nrk, NRH is phosphorylated by adenosine kinase (AK) and converted to NMNH and subsequently to NADH and NAD + [ 26 , 27 ]. NRH can improve mitochondrial function and regulate oxidative stress [ 28 ].…”
Section: Extracellular Nad + Precursorsmentioning
confidence: 99%